IMPLEMENTASI KEBIJAKAN KREDIT USAHA RAKYAT DALAM MENGEMBANGKAN USAHA, MIKRO, KECIL DAN MENENGAH DI KECAMATAN KOTO BARU KABUPATEN DHARMASRAYA - Puryanto Puryanto; Novi Helmidani (Ensiklopedia of Journal, 2019)
The implementation of people's business credit policies in developing micro, small and medium enterprises in Koto Baru Subdistrict, Dharmasraya Regency has not been fully optimal. This is still found to be a limiting factor from the distribution of the people's business credit program. Based on the research carried out, it was concluded that the implementation of the people's business credit policy in developing small and medium enterprises in the Koto Baru sub-district of Dharmasaraya District had not fully run optimally. This is still found to be an inhibiting factor from the distribution of the people's business credit program, just as the KUR program which is intended for small and medium micro business actors can still be enjoyed by non-MSME actors, and also there are still people who use people's Business Credit funds instead intended for productive business. Another factor that inhibits the implementation of KUR in Koto Baru Subdistrict is the low participation of the people who utilize the KUR program, lack of information or ignorance of the public about the existence of the KUR program in Koto Baru Subdistrict, and there is a public perception that dealing with banks will be complicated and complicated. Later, the existence of a policy on People's Business Credit is very helpful for the people in the Koto Baru sub-district, Dharmasraya Regency.